Legal Aspects of Government Action in the Indictment of the Corruption Eradication Commission Public Prosecutor - Nirahua, Garciano; Holle, Erick Stenly; Sedubun, Victor Juzuf (Bacarita Law Journal, 2021)
Law of the Republic of Indonesia number 19 of 2019 concerning the second amendment to law number 30 of 2002 concerning the Corruption Eradication Commission was formed with the aim of increasing the efficiency and effectiveness of efforts to eradicate corruption. In carrying out its duties, the Corruption Eradication Commission was given the authority to conduct investigations, investigations, and prosecutions (indictments) of corruption crimes involving law enforcement officers, state administrators, and other people related to corruption crimes committed by law enforcement officers or state administrators.